2011
DOI: 10.1590/s1806-37132011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento farmacológico da DPOC

Abstract: ResumoAproximadamente sete milhões de brasileiros acima de 40 anos são acometidos pela DPOC. Nos últimos anos, importantes avanços foram registrados no campo do tratamento medicamentoso dessa condição. Foi realizada uma revisão sistemática incluindo artigos originais sobre tratamento farmacológico da DPOC publicados entre 2005 e 2009, indexados em bases de dados nacionais e internacionais e escritos em inglês, espanhol ou português. Artigos com tamanho amostral menor de 100 indivíduos foram excluídos. Os desfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 85 publications
0
12
0
13
Order By: Relevance
“…Therefore, patients with COPD that is more severe predominated, the benefits of maintenance treatment being greater in such patients. ( 5 ) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, patients with COPD that is more severe predominated, the benefits of maintenance treatment being greater in such patients. ( 5 ) …”
Section: Discussionmentioning
confidence: 99%
“…( 13 - 16 ) A recent systematic review showed that there is evidence for IC use only in patients with severe COPD and symptoms and in those with moderate or severe COPD, symptoms, and more than two COPD exacerbations per year. ( 5 ) Incorrect prescription of LABA + IC is common among patients with moderate disease treated at primary or secondary health care facilities. ( 17 - 20 ) Studies have shown that 45% of patients with moderate COPD receive ICs only, whereas 60% receive LABA + IC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 1 ) The type of inhaled medication recommended for individuals with emphysema also deserves attention because it does not seem to be in accordance with the recommendations. ( 2 , 26 ) Finally, the implementation of new policies for the free distribution of these drugs will meet the needs identified in the present study, because although few individuals reported lack of financial resources to purchase an inhaler as the reason for not using an inhaler, inhaler use is lowest among those of lowest socioeconomic status. …”
Section: Discussionmentioning
confidence: 73%
“…A recent systematic review highlighted that ICs should be used only in those with frequent exacerbations. ( 26 ) According to the Global Initiative for Chronic Obstructive Lung Disease guidelines, ICs should be reserved for those belonging to high-risk groups. ( 2 ) In our study, we did not evaluate the frequency or type of symptoms that can lead to an estimation of the severity of COPD; however, data from a previous population-based study showed that those for whom ICs are indicated account for only approximately 1% of all COPD patients.…”
Section: Discussionmentioning
confidence: 99%